Odpowiedzi

Najlepsza Odpowiedź!
2010-02-06T22:12:07+01:00
Metoda podstawiania
a)
5x+2y=2,7
x+5y=1

5x+2y=2,7
x=1-5y

5(1-5y)+2y=2,7
5-25y+2y=2,7
-23y=-2,3
y=0,1

x=1-5*0,1
x=1-0,5
x=0,5

b)
2x+y=2,5
3x+4y=5

y=2,5-2x
3x+4(2,5-2x)=5
3x+10-8x=5
-5x=-5
x=1

y=2,5-2*1
y=2,5-2
y=0,5

c)
1/2x-1/4y=4|:1/2
1/3x+1/2y=2

x-1/2y=8
1/3x+1/2y=2

x=8+1/2y
1/3(8+1/2y)+1/2y=2

8/3+1/6y+1/2y=2
2/3y=-2/3
y=-1

x=8+1/2*(-1)
x=8-1/2
x=7,5

d)
2x+4y=-7|:2
4x-3y=8

x+2y=-3,5
4x-3y=8

x=-3,5-2y
4(-3,5-2y)-3y=8
-14-8y-3y=8
-11y=22
y=-2

x=-3,5-2*(-2)
x=-3,5+4
x=0,5

e)
y=2x-1
3(x+2)=5(y-2)

y=2x-1
3x+6=5y-10

y=2x-1
3x-5y=-16

3x-5(2x-1)=-16
3x-10x+5=-16
-7x=-21
x=3

y=2*3-1
y=6-1
y=5

f)
(x+3)/2-(y+2)/3=-1
x+4y=1

3x+9-2y+4=-1
x=1-4y

3x-2y=-14
3(1-4y)-2y=-14
3-12y-2y=-14
-14y=-14
y=1

x=1-4*1
x=1-4
x=-3

g)
2(x+3)-3(y-2)=-4
3(x+y+2)=2(2x+y+6)

2x+6-3y+6=-4
3x+3y+6=4x+2y+12

2x-3y=-16
-x+y=6

2x-3y=-16
y=6+x

2x-3(6+x)=-16
2x-18-3x=-16
-x=2
x=-2

y=6+(-2)
y=4

h)
x-2²+2y=x-1²+y-1
2x=3y

x+4+2y=x+1+y-1
2x=3y

y=-4

2x=3*(-4)
2x=-12
x=-6

1 5 1